Numerical simulations of fluid dynamics and mixing in a large shallow bubble column: effects of the sparging pipe allocations for multiple-pipe gas distributors. (3rd August 2009) - Li, Guang; Cai, Qingbai; Dai, Gance; Yang, Xiaogang
Numerical simulations of gas-liquid flow in a bubble column of 800 mm in diameter using two-fluid model and multi-size-group (MUSIG) model were conducted to investigate the effect of allocation of sparging pipes in gas distributors on hydrodynamic flow, gas hold-up, mixing characteristics, turbulence and bubble size. In the simulation, six different arrangements were assessed, which four-sparging pipes are mounted to a gas distributor with the allocation ring to bubble column ratios (d/DT) being 0.3, 0.37, 0.4, 0.5, 0.6 and 0.7, respectively. The simulation results have clearly demonstrated that the allocation of sparging pipes to the gas distributor has an important impact on gas hold-up and mixing characteristics. It was found from the simulations that the mixing time and overall gas hold-up increase initially with the increase of d/DT but decrease with further increase of d/DT. As a result, it was revealed that the optimum value of d/DT is around 0.4 for the highest overall gas hold-up and is confirmed by the experiment. It was also indicated from the simulation that d/DT of 0.5 yields the maximum mixing time.